Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 9 - Section 9.4 - Properties of Logarithms - Exercise Set: 25

Answer

$2 - \frac{1}{2}\log_6{(x+1)}$

Work Step by Step

RECALL: (1) $\log{(b^c)}=c \cdot \log{b}$ (2) $\log_b{(xy)} = \log_b{x} + \log_b{y}$ (3) $\log_b{(\frac{x}{y})}=\log_b{x} - \log_b{y}$ Use rule (3) above to obtain: $=\log_6{36}-\log_6{(\sqrt{x+1})}$ Note that $\sqrt{x+1} = (x+1)^{\frac{1}{2}}$ and $36=6^2$. Thus, the expression above is equivalent to: $=\log_6{(6^{2})}-\log_6{(x+1)^{\frac{1}{2}}}$ Use rule (1) above to obtain: $=2\log_6{6} - \frac{1}{2}\log_6{(x+1)}$ Use the rule $\log_b{b} = 1$ to obtain: $=2 \cdot 1 - \frac{1}{2}\log_6{(x+1)} \\=2 - \frac{1}{2}\log_6{(x+1)} $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.